Omadacycline for the treatment of patients with Legionella pneumophila pneumonia after experiencing liver dysfunction: case series - Zhu, Ani; Ma, Qian; Liu, Zhiyan (Frontiers in Microbiology, 2024)
Antibiotics frequently induce abnormal liver function. Omadacycline is a novel aminomethylcycline antibiotic, which shows potent activity against Gram-positive and Gram-negative aerobic, anaerobic, and atypical (including Legionella pneumophila) bacteria. Of note, omadacycline is tolerable in most patients with liver impairment. However, evidence regarding the application of omadacycline in patients with Legionella pneumophila pneumonia after experiencing liver dysfunction is scarce. The current study reported 6 cases of patients with Legionella pneumophila pneumonia receiving omadacycline as subsequent antibiotics. These 6 cases were admitted to the hospital for pneumonia and received antibiotic therapy, including piperacillin-tazobactam, imipenem, meropenem, and moxifloxacin. After receiving these antibiotics, increased liver enzymes were noted. Although hepatoprotective therapy (such as magnesium isoglycyrrhizinate and glutathione) was given, the liver function was still abnormal. According to metagenomic next-generation sequencing, these patients were diagnosed with Legionella pneumophila pneumonia. Considering the abnormal liver function, the antibiotic therapy was switched to omadacycline-containing antibiotic therapy. After that, liver function was improved, and the infection was ameliorated. Ultimately, all patients were discharged from the hospital, including 2 patients who achieved complete clinical symptomatic improvement and 4 patients who achieved partial clinical symptomatic improvement. In conclusion, this study emphasizes the successful treatment of switching to omadacycline after experiencing abnormal liver function in patients with Legionella pneumophila pneumonia. This study suggests that omadacycline may serve as an optional antibiotic for patients with Legionella pneumophila pneumonia, especially when occurring liver dysfunction. However, more clinical studies are required to validate our findings.